The Organizational Capabilities of Tanjungpinang City Hospital in Facing Changes in Accreditation Regulations and the JKN KRIS to Improve the Quality of Health Services - N. Nofitasari; Armauliza Septiawan; Fitri Kurnianingsih (Manunggal Halim Jaya, 2026)
Changes to national health service regulations, particularly through the latest hospital accreditation standards and the National Health Insurance Standard Inpatient Class (KRIS JKN) policy, require regional hospitals to improve their organizational adaptability so that they can continue to provide quality and sustainable services. This study aims to answer the question: how capable is the Tanjungpinang City Hospital organization in responding to regulatory changes? This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews with purposively selected key informants, supported by document analyses. Data analysis employed the interactive model of Miles, Huberman, and Saldana, which encompasses data condensation, data presentation, and conclusion drawing through the triangulation of sources and methods. The operational capabilities in this study included human resource management, clinical service flow, hospital information systems, financial management, and service quality assurance mechanisms. The results show that the Tanjungpinang City Hospital has demonstrated managerial commitment through the renewal of standard operating procedures (SOPs), strengthening of organizational structures, and digitization of health services. Innovation capabilities are evident through facility improvements, the development of specialist services, and enhancing human resource competencies. However, operational capabilities still face obstacles, particularly in integrating electronic medical record systems with clinical service needs. The findings of this study imply that integrated organizational capacity building is necessary to improve the quality of regional hospital services and support institutional readiness to face the dynamics of future healthcare regulations.